Immunologically Active Components in Human Milk and Development of Atopic Disease, With Emphasis on Food Allergy, in the Pediatric Population - Rajani, Puja S.; Seppo, Antti E.; Järvinen, Kirsi M. (Frontiers in Pediatrics, 2018)
Breast-feeding is currently recommended to prevent the development of allergic diseases; however, data are conflicting and mechanisms are unclear. The immunomodulatory composition of breast milk is poorly characterized and varies between mothers. We and others have shown that high levels of breast milk IgA and certain cytokines and human milk oligosaccharides are associated with protection against food allergy in the infant, but it is unclear whether they are responsible for or simply biomarkers of the vertical transfer of protection. Because breast milk has pre- and probiotic properties, the anti-allergy protection afforded by breast milk may be due to its control on the developing gut microbiome. In mice, breast milk IgA supports gut homeostasis and shapes the microbiota, which in turn diversifies the intestinal IgA repertoire that reciprocally promotes the diversity of gut microbiome; these mechanisms are poorly understood in humans. In addition, several human milk bioactives are immunostimulatory, which may in part provide protection against allergic diseases. The regulation of immunologically active components in human milk is incompletely understood, although accumulating evidence suggests that IgA and cytokines in breast milk reflect maternal exposures. This review summarizes the current literature on breast milk components that have been associated with protection against food allergy and related allergic disorders in early childhood and discusses the work relating to regulation of these levels in breast milk and possible mechanisms of action.